Transsexuality and sport: the brazilian case of Tiffany Abreu - Rafael Marques Garcia; Erik Giuseppe Barbosa Pereira (Universidad de Antioquia, 2020)
Transsexuality and/or sport is a combination that has caused fervent debates in society. In the scientific community, this issue, since it is controversial, and still little explored, presents studies in the ascendancy phase. Objective: To describe and to analyze the trajectory of the transsexual athlete Tifanny Abreu in high-performance volleyball and her process of resignification in sport. Methodology: Descriptive and qualitative, characterizing a case study, through an interview with a semi-structured script and two reports. Results: We find resistances in the revelation, formation, and performance of Tifanny due to heteronormative precepts, discriminatory, and excluding, which ignore queer performativity.